ARTIFICIAL INTELLIGENCE DAN PENDIDIKAN ERA SOCIETY 5.0 - Riskey Oktavian; Riantina Fitra Aldya; Rio Febrianto Arifendi (Universitas Tribhuwana Tunggadewi, 2023)
This study aims to describe artificial intelligence (AI) and education in the era of society 5.0. This research is a descriptive-qualitative research with a method in the form of journal meta-analysis by complementing and comparing previous information through literature review using data from 22 journal articles to be collected then further studied and analyzed related to the results of their findings and draw a conclusion. This study examines about: (1) artificial intelligence (AI) in the field of education; (2) the role and position of artificial intelligence (AI) in the field of education; (3) the advantages and disadvantages of artificial intelligence (AI) in the field of education; and (4) artificial intelligence (AI) in the field of education to face the era of Society 5.0., which is to overcome the challenges and problems of the times quickly. AI has the advantage of being able to quickly create and score content, automate tasks in education, but it also has the disadvantage of having risks in handling privacy issues, algorithmic bias, and transparency controls. AI itself cannot replace the position of teachers because it cannot monitor student development significantly, how character morally and emotionally, so it would be better if AI is used as a tool that can help teachers do learning and also an emotional approach in building student character to face the era of Society 5.0.